A pharmacovigilance study of antiretroviral therapy in HIV positive out patients at a tertiary care teaching hospital - Reddy T., Muneeshwar; T. S., Durga Prasad; Reddy, Sravani Gundramy; Dudu, Sravani; Mohan, Rameela; Punnamaraju, Kali Prasanna; Dudekula, Seetharam Babu (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Anti-Retroviral Therapy regimen (ART) is the only treatment option for treating the HIV positive patients for improving the immune system by increasing the CD4 cells. But eventually these medications lead to development of some Adverse Drug Reactions (ADRs) in seropositive patients under treatment. Methods: A prospective observational study was conducted for 6 months from March to August 2018 at ART Centre, Sri Venkateswara Ramnarayan Ruya Government General Hospital (SVRRGGH), Tirupati. Results: Out of 216 ADRs identified, majority where identified in females (54.35%). Most common regimen caused ADR was tenofovir+ lamivudine+ efavirenz (TLE) (55.55%). Data were analysed using the chi-square test were P-value was found to be 0.0024. Majority of ADRs were found in patients of age group between 31-35years was found to be 45 (20.83%) followed by age group between 41-45years was found to be 40 (18.51%). Most of the ADRs were related to central nervous system (27.31%) followed by metabolic disorders (26.38%), hematologic system (23.14%), gastrointestinal system (12.96%), dermatologic system (9.25%), renal system (0.46%) and musculoskeletal system (0.46%). On evaluation of WHO-UMC causality of ADRs, majority were found to be possible (78.7%). The Hartwig and Siegel’s severity assessment scale showed that most of the ADRs were mild (64.42%). The Schumock and Thornton preventability scale showed that 50.92% patients ADRs were probably preventable. Conclusions: As most of the ADRs were observed in patients receiving TLE regimen. So, patients receiving TLE regimen need intensive monitoring. Doctors, nurses, pharmacist must focus on early detection and prevention of ADRs, based on their severity.